Responsabilidade social da empresa: a área de gestão de pessoas como mediadora entre a organização e a comunidade - Amaral, Roberto Galassi (2007)
The inclusion of responsibility for the management and execution of social projects in the agenda of human resources has brought in both synergy and challenges. This area, historically created aiming at the management of employees in a company, assists and supports now two distinct audiences. The first, inherently related to a work agreement and which is oriented by the organizational policies, management principles and company control, and the second which does not follow hierarchy. This research has then attempted to contribute to the implementation of social responsibility in the company, especially within the management of relations with the community initiated by the human resources area. In that sense, it has made a theoretical analysis based on management sciences, examining the context of corporate management, the management and the manager, identifying corporate social responsibility as a model of corporate management. It has systematized concepts that come around it such as: Corporate Philanthropy, Citizen Corporation, Private Social Investment, Marketing of Social Causes. It has also examined the interaction between business ethics and the third sector within this management model. This paper has gathered reflections on the history of the performance of the human resources area, people management models and the interaction that lies within the area and the socially responsible management. It has presented a concept model to support the processes of role assignment between positions in human resources and corporate management. To generate understanding about all these issues, this study has been based upon research made in the human resources departments in ten different companies in the metropolitan area of São Paulo. As a general objective, it verified the way the area of human resources has been managing corporate social responsibility concerning the company s relations with the community. Some specific objectives were equally sought. First, it tried to verify the understanding of this subject from the point of view of managers and directors of the researched area, as well as its implementation as a model of management. Second, it attempted to investigate some motivational profiles in the companies, how these motivations are translated into practical actions within the community and how they are managed. Third, it tried to get to know the perception of organizations about the challenges set upon social actions, when performed by the company and managed by the human resources area. Finally, some recommendations have been made regarding researches on the real implementation of this model of management. A favorable conclusion was drawn towards the development of competences in the professionals of human resources in order to potentialize their new role as articulators between private and public interests